The suffering traveller and the Romantic imagination - Thompson, Carl (Clarendon, 2007)
Thompson explores the romance that can attach to the notion of suffering in travel, and the importance of the persona of 'suffering traveller' for Romantic writers and travellers. He considers how and why the Romantics typically chose to imitate the hapless protagonists of these accounts.
10.1093/acprof:oso/9780199259984.001.0001
Keywords: Wordsworth; William; Byron; George Gordon Byron; Travelers' writings; English; Travel in literature; Explorers in literature; Adventure and adventurers in literature; Shipwrecks in literature; Travel; Romanticism